The Glucotoxicity Protecting Effect of Ezetimibe in Pancreatic Beta Cells via Inhibition of CD36 - Yoon, Ji Sung (J Korean Med Sci, 2016)
Inhibition of CD36, a fatty acid transporter, has been reported to prevent glucotoxicity and ameliorate high glucose induced beta cell dysfunction. Ezetimibe is a selective cholesterol absorption inhibitor that blocks Niemann Pick C1-like 1 protein, but may exert its effect through suppression of CD36. We attempted to clarify the beneficial effect of ezetimibe on insulin secreting cells and to determine whether this effect is related to change of CD36 expression. mRNA expression of insulin and CD36, intracellular peroxide level and glucose stimulated insulin secretion (GSIS) under normal (5.6 mM) or high glucose (30 mM) condition in INS-1 cells and primary rat islet cells were compared. Changes of the aforementioned factors with treatment with ezetimibe (20 μM) under normal or high glucose condition were also assessed. mRNA expression of insulin was decreased with high glucose, which was reversed by ezetimibe in both INS-1 cells and primary rat islets. CD36 mRNA expression was increased with high glucose, but decreased by ezetimibe in INS-1 cells and primary rat islets. Three-day treatment with high glucose resulted in an increase in intracellular peroxide level; however, it was decreased by treatment with ezetimibe. Decrease in GSIS by three-day treatment with high glucose was reversed by ezetimibe. Palmitate uptake following exposure to high glucose conditions for three days was significantly elevated, which was reversed by ezetimibe in INS-1 cells. Ezetimibe may prevent glucotoxicity in pancreatic β-cells through a decrease in fatty acid influx via inhibition of CD36.